Ferroelectric Polymer Nanofibers Reminiscent of Morphotropic Phase Boundary Behavior for Improved Piezoelectric Energy Harvesting (Small 15/2022). Issue 15 (14th April 2022) - Park, Jiseul; Lim, Yeong‐won; Cho, Sam Yeon; Byun, Myunghwan; Park, Kwi‐Il; Lee, Han Eol; Bu, Sang Don; Lee, Ki‐Tae; Wang, Qing; Jeong, Chang Kyu
Abstract : Energy Harvesting In article number 2104472, Qing Wang, Chang Kyu Jeong, and co‐workers study the enhancement of piezoelectric device performance using the morphotropic phase boundary behavior of polyvinylidene fluoride‐based polymers related with its relaxor property. Moreover, it is proved that the characteristics are maintained in the nanofiber feature.